2018
DOI: 10.1139/apnm-2018-0050
|View full text |Cite
|
Sign up to set email alerts
|

Acute beetroot juice administration improves peak isometric force production in adolescent males

Abstract: The purpose of this study was to examine the effects of acute beetroot juice (BR) administration on repeated sprint performance and isometric force production in adolescent males. Twelve male adolescents (age, 16.8 ± 1.0 years; height, 178.8 ± 9.2 cm; mass, 74.8 ± 12.5 kg; peak height velocity, 2.53 ± 1.2 years) participated in this double-blind, placebo-controlled, crossover designed study. Participants consumed 2 × 70 mL of BR (∼12.9 mmol NO; Beet It Sport) or a nitrate-depleted placebo (PL) at 2.5 h prior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 41 publications
3
46
0
Order By: Relevance
“…In relation to this, other studies [ 38 , 39 ] demonstrated that BJ supplementation enhanced angular velocity and muscle power in knee extension evaluated in different populations, these results supporting the hypothesis that NO 3 − influences the contractile properties of human muscle [ 38 ] according to previous studies in rats [ 17 ]. A previous study by Bender et al [ 40 ] demonstrated that acute BJ supplementation increased peak isometric force output in adolescent men, although they used a higher dose and consumption time than ours: 2 × 70 mL of BJ (∼12.9 mmol·L −1 NO 3 − ) at 2.5 h prior to performing test. In addition to this, Whitfield et al [ 41 ] reported that BJ supplementation increased force production and peak twitch tension albeit using a multiday dosing protocol.…”
Section: Discussionmentioning
confidence: 80%
“…In relation to this, other studies [ 38 , 39 ] demonstrated that BJ supplementation enhanced angular velocity and muscle power in knee extension evaluated in different populations, these results supporting the hypothesis that NO 3 − influences the contractile properties of human muscle [ 38 ] according to previous studies in rats [ 17 ]. A previous study by Bender et al [ 40 ] demonstrated that acute BJ supplementation increased peak isometric force output in adolescent men, although they used a higher dose and consumption time than ours: 2 × 70 mL of BJ (∼12.9 mmol·L −1 NO 3 − ) at 2.5 h prior to performing test. In addition to this, Whitfield et al [ 41 ] reported that BJ supplementation increased force production and peak twitch tension albeit using a multiday dosing protocol.…”
Section: Discussionmentioning
confidence: 80%
“…Data extraction was then independently performed by the same three authors. Specifically, study design, sample size, subject characteristics, form, dose, and duration of NO 3 − supplementation, placebo characteristics, experimental procedures, and testing conditions were obtained from the text of eligible papers [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]. Effect sizes (ES), i.e., Hedge's g, for NO 3 − -induced changes in peak or maximal power were calculated from either 1) the means and SDs for the NO 3 − and placebo trials along with the exact P values for the within-subject comparison [49,53,55,58,60], or 2) anonymized individual subject data obtained from the authors [42-48, 50-52, 54, 56, 57, 59].…”
Section: Study Selection and Data Extractionmentioning
confidence: 99%
“…Since data from the 12 subjects in our original study [43] were also included in a subsequent report [50], only the results from the eight additional subjects in the latter study were used in the meta-analysis. A number of the studies employed a repeated sprint cycling protocol and/ or only reported the mean power during a Wingate-style test [51,52,54,55,60]. In such instances, peak power from the first sprint was obtained from the authors and utilized in the meta-analysis.…”
Section: Study Selection and Data Extractionmentioning
confidence: 99%
“…NO 3 − supplementation has been reported to increase force production at low stimulation frequencies in some (≤20 Hz) [ 22 , 23 , 24 ], but not all studies [ 25 , 26 ]. Although dietary NO 3 − supplementation has been reported to improve maximal voluntary contractile force during a mid-thigh pull [ 27 ], most studies have not observed an increase in maximal voluntary isometric contractile force when contracting the knee extensors [ 19 , 22 , 23 , 25 , 26 , 28 , 29 ]. Acute NO 3 − ingestion has been reported to enhance peak torque during isokinetic dynamometry at high but not low angular velocities [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%